2005
DOI: 10.1080/10473289.2005.10464713
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Emissions with Time and Temperature to Predict Worst-Case Emissions from Open Liquid Area Sources

Abstract: The two primary factors influencing ambient air pollutant concentrations are emission rate and dispersion rate. Gaussian dispersion modeling studies for odors, and often other air pollutants, vary dispersion rates using hourly meteorological data. However, emission rates are typically held constant, based on one measured value. Using constant emission rates can be especially inaccurate for open liquid area sources, like wastewater treatment plant units, which have greater emissions during warmer weather, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…Therefore, we could suppose that, since the sulfur was shipped in liquid form (sulfur melting point 113 8C), H 2 S easily passes from the liquid to gas phase in the tanker due to its high vapor pressure (252 psi at 21 8C) and low boiling point (À60 8C) (see Table 3). Additionally, its low Henry's constant (8.7 Â 10 À2 M/atm) confirmed its low solubility [38,39] which is similar to those reported for other gases such as O 2 (K H = 1.3 Â 10 À3 M/atm) and CO 2 (K H = 3.4 Â 10 À2 M/atm) [40].…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, we could suppose that, since the sulfur was shipped in liquid form (sulfur melting point 113 8C), H 2 S easily passes from the liquid to gas phase in the tanker due to its high vapor pressure (252 psi at 21 8C) and low boiling point (À60 8C) (see Table 3). Additionally, its low Henry's constant (8.7 Â 10 À2 M/atm) confirmed its low solubility [38,39] which is similar to those reported for other gases such as O 2 (K H = 1.3 Â 10 À3 M/atm) and CO 2 (K H = 3.4 Â 10 À2 M/atm) [40].…”
Section: Discussionsupporting
confidence: 77%
“…21,25,30,31 However, none of these studies estimated the accuracy of models used. A comparative study between the CALPUFF model and the ISCST3 Gaussian dispersion models examined downwind odors and source emission rates and concluded that both models are unable to predict peak odor concentrations by using a constant average emission rate, and odor emission rates obtained by back-calculating fluxes using CALPUFF and ISC models with the same field measurements of downwind odor concentrations are significantly different.…”
Section: Emission Rate Values and Air Quality Modelingmentioning
confidence: 98%
“…Emission rates for a wastewater odor study are measured on a cooler day and input directly into a dispersion model as constant values, odor impact will likely be underestimated. Nagaraj and Sattler (2005) Characterization of the newly synthesized material was performed using BET, XRD, TEM, SEM and DRIFTS techniques, in addition to its carbon and nitrogen elemental composition.…”
Section: Physicochemical Treatmentmentioning
confidence: 99%